Mapping the Complexities of Effective Leadership for Social Justice Praxis in Urban Auckland Primary Schools - Sharona Jayavant (MDPI AG, 2016)
This empirical research is about strengths-based leadership practices that seek to explore leadership for social justice and equity in New Zealand's culturally and linguistically diverse educational and social landscape. Similar to the diversity in other countries, where leaders demonstrate culturally responsive leadership practices in their quest to educate diverse democracies. This inquiry examines the characteristics and behaviours of effective leadership for social justice and equity for student academic achievement in urban Auckland primary schools. A qualitative, comparative case study, combined with the theoretical framework of applied critical leadership from theories of transformational leadership, critical pedagogy and critical race theory (perspective lens) guided the research methods. The research findings presented several applied critical leadership characteristics that highlighted the complexities of leading for social justice in urban Auckland primary schools. A distinct phenomenon was leader's axiological philosophy (values, beliefs and morals) underpinning their leadership that was culturally responsive to the diversity in their educational contexts. These findings suggest the need for research and scholarship yet to be done in this largely unexplored educational leadership academic space.